Pengaruh Content Marketing Terhadap Keputusan Pembelian Album Fisik (Studi Pada Komunitas Carat di Surabaya) - A'yun, Qurrota (The Commercium, 2023)
This research aims to find out the effect between content marketing and physical album buying decision. The population in this research was all Seventeen fans who are joined the Carat Community in Surabaya. The samples in this research were Carat Community in Surabaya as many as 152 people taken using Slovin formula. This research is a quantitative study with the type of positivistic paradigm. Positivistic paradigm in this research aims to know correlation between cause-effect in social phenomena. The data collection techniques in this research uses questionnaires distributed to Seventeen fans who are joined the Carat Community in Surabaya. The validity test technique was analyzed using Pearson Product Moment. The reliability test in this research used the techniques of the Cronbach Alpha, content marketing instrument has a reliability value of 1,027 and buying decision instrument has a reliability value of 0,871. Data analysis technique in this research used Simple Linear Regression. The result of this research indicate that content marketing has an effect as many as 0,350 or 35% to physical album buying decision. Based on the results of data analysis, it can be concluded there is an effect between content marketing and physical album buying decision of Carat Community in Surabaya. This research is expected to be a literacy and reference related to content marketing which is part of marketing communications to students, universities, and society. Keywords: Content Marketing, Buying Decision, Physical Album